The Variation Effect of Collector Tilt Angle on the Heat Pipe Solar Collector Performance - Abdulsalam D. M. Hassan; Rwaa Alaa Hussein (Wasit Journal of Engineering Sciences)
The thermal performance of FPHPSC has been studied experimentally and theoretically. The collector consists of copper absorber plate, single glass cover, glass wool insulation and aluminum case, ten wickless heat pipes of 12.7 mm inner diameter. The experimental studies of collector performance have been performed on four different CTA (22°, 32°, 45° and 60°). The relation between the solar intensity and the collector energy losses are also discussed. The collector are tested under the climate condition of Kut city (32.602 latitude and 45.752 longitude). It is investigated that the increasing of CTA increase the efficiency of collector up to certain limit after that the efficiency decreases with the increasing of tilt angle of collector. A computer program which is based on VISUAL BASICE language (version 6) is made for the theoretical analysis. The experimental results agree reasonably with the theoretical predictions.